2009
DOI: 10.1111/j.1365-2044.2009.06135.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the validity of SOFA score based triage in H1N1 critically ill patients during an influenza pandemic

Abstract: SummarySequential Organ Failure Assessment (SOFA) score based triage of influenza A H1N1 critically ill patients has been proposed for surge capacity management as a guide for clinical decision making. We conducted a retrospective records review and SOFA scoring of critically ill patients with influenza A H1N1 in a mixed medical‐surgical intensive care unit in an urban hospital. Eight critically ill patients with influenza A H1N1 were admitted to the intensive care unit. Their mean (range) age was 39 (26–52) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 21 publications
2
59
0
6
Order By: Relevance
“…However, Khan and colleagues [12] showed 63% survival in their SOFA defined poor prognosis group with H1N1 with a mean LOS of 11 (range of 3 to 17) days. This presents a problem if we assume that the DOH intended that the triage tool be applied to limit those 12.4 days by early palliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Khan and colleagues [12] showed 63% survival in their SOFA defined poor prognosis group with H1N1 with a mean LOS of 11 (range of 3 to 17) days. This presents a problem if we assume that the DOH intended that the triage tool be applied to limit those 12.4 days by early palliation.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of H1N1 pandemic influenza has not occurred as expected. As data has become accessible, reports suggest that SOFA score may not be a good discriminator of outcome in this cohort of patients [12,13]. Thus, its suitability as a means to assist in the triage of H1N1 patients has been called into question.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has shown that obesity is a risk factor for requiring a long duration of ventilator support in ICU settings (Akinnusi, Pineda, and Solh 2008; Centers for Disease Control and Prevention 2009). A small study from the United Kingdom during the H1N1 pandemic showed that SOFA scoring used to triage ICU patients would have required the discontinuation of ICU care for all patients requiring mechanical ventilation in the cohort (five out of eight patients) because SOFA scores forty-eight hours after admission indicated that such patients were too ill to continue using up scarce resources (Khan, Hulme, and Sherwood 2009). The only patients who would have received continued treatment were the three in the cohort who did not require mechanical ventilation (ibid.…”
Section: Relational Factors-doing Poorly On Sofamentioning
confidence: 99%
“…It might be possible to give patients listed on the registry of vulnerable or oppressed groups a pass at this stage, such that they could not be withdrawn from ICU care after the forty-eighthour reassessment, even if their SOFA scores are poor. The study by Khan, Hulme, and Sherwood (2009) shows that some patients designated for withdrawal of lifesaving care at forty-eight hours because practices, and ways of thinking that address injustice. Amending pandemic triage protocols to prevent the possibility that they will be used to reinforce injustice is merely a second-best solution.…”
Section: Possible Amendmentsmentioning
confidence: 99%
“…The Table 4 prioritization tool utilizes the Sequential Organ Failure Assessment (SOFA) score [17, 18], which has limitations and has not yet been validated. Although SOFA day-1 scores have been shown in recent H1N1 patients to be significantly associated with 28-day and overall mortality [21, 26], little improvement in SOFA scores of influenza patients between admission and day 3 raises the question as to what specific interval for re-assessment is most appropriate for patients with influenza [27]. However, it is important to note that the triage protocol must apply to all critically ill patients with a variety of illnesses or injuries, and re-assessment at 48 h did show an ability to predict outcomes [17].…”
Section: Concepts Of Operationsmentioning
confidence: 99%